Rural Credit Access and Household Economic Performance: The Mediating Roles of Food Security and Household Resilience - Fikiru Temesgen Gelata (Canadian Journal of Business, Economics and Health Management, 2026)
Access to financial resources remains an important challenge for many rural households, limiting their ability to improve economic conditions and cope with unexpected shocks. While previous studies have documented the economic benefits of rural credit, less attention has been given to the mechanisms through which credit access contributes to household economic performance. This study examines the relationships among rural credit access, food security, household resilience, and household economic performance. A quantitative cross-sectional survey was conducted among 312 rural households. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that rural credit access positively influences food security, household resilience, and household economic performance. Food security and household resilience were also found to significantly enhance household economic performance. Furthermore, both variables partially mediated the relationship between rural credit access and household economic performance. Household resilience emerged as the strongest predictor of economic performance among the examined factors. The findings suggest that the benefits of rural credit extend beyond direct financial support by strengthening households' ability to secure essential resources and adapt to economic challenges. The study highlights the importance of integrating financial inclusion initiatives with food security and resilience-building programs to promote sustainable improvements in rural household welfare.